Comparison of phenotypic and molecular tests to identify lactic acid bacteria - Moraes, Paula Mendonça; Perin, Luana Martins; Silva Júnior, Abelardo; Nero, Luís Augusto (Brazilian Journal of Microbiology, 2012)
Twenty-nine lactic acid bacteria (LAB) isolates were submitted for identification using Biolog, API50CHL, 16S rDNA sequencing, and species-specific PCR reactions. The identification results were compared, and it was concluded that a polyphasic approach is necessary for proper LAB identification, being the molecular analyzes the most reliable.
Keywords: Lactic acid bacteria; Identification; 16sDNA; PCR; Biolog; API